Analytical Differentiation of Wines from Three Terroirs Located in a Warm Winegrowing Area Based on Their Volatilome - José Miguel Fuentes-Espinosa; Raquel Muñoz-Castells; Jaime Moreno-García; Teresa García-Martínez; Juan Carlos Mauricio; Juan Moreno (Molecules)
This research aims to identify aroma compounds, their combinations, and statistical relationships to classify and characterize wines produced in small, defined areas known as “terroirs”, which share edaphoclimatic characteristics grape varieties, viticultural practices, harvest timing, and winemaking processes. The goal is to deepen the understanding of the relationship between the terroir and wine typicity. This study analyzed the contents based on enological parameters, the major and minor volatile compounds of the young wines produced in three wineries across two vintages, using the Pedro Ximenez white grape variety cultivated in different terroirs within the same quality zone. Statistical tools, such as Multiple Variable Analysis (MVA) and Principal Component Analysis (PCA), were employed to identify significant differences in the volatilomes of wines. PCA effectively differentiated wines from each terroir and vintage using scores from the first two principal components, calculated based on the absolute concentrations of 12 major volatile compounds and 3 polyols. Conversely, PCA based on the concentrations of 52 minor volatile compounds showed a strong ability to classify wines by vintage year. The minor volatile contents of wines from 2 vintages, grouped into 9 chemical families, provide distinct fingerprints that enable wines to be distinguished by terroir. The results underscore the chemical basis underlying terroir typicity in a production zone within a warm Protected Denomination of Origin (PDO).